Entropic lifespan: Disorder and transformation in human life from birth to death - Goshu, Belay (Brazilian Journal of Science, 2025)
This study constructs an interdisciplinary framework to investigate entropy’s role across human life (biological, psychological, social) and natural systems, grounded in the thermodynamic principle of increasing disorder. The background reveals entropy’s relevance in aging, cognition, social roles, and ecosystems, yet a cohesive model remains undeveloped. The purpose is to integrate these domains, analyzing entropy from birth/emergence to death/collapse. Methods employ a mixed-model simulation with a modified Shannon entropy approach, tracking entropy in cellular degradation, cognitive disorder/growth, role dissolution/reorganization, and ecosystem decay over 100 years, with data evaluated at key stages (0, 20, 40, 70, 100 years). Findings indicate a synchronized entropy increase: biological from 0.10 to 4.00, psychological from 0.10 to 3.50, social from 0.10 to 3.00, and natural from 0.10 to 3.50, with midlife dips in psychological and social entropy due to adaptive processes. Strong correlations (e.g., biological vs. natural, r = 0.96) affirm a universal entropic pattern. The conclusion establishes entropy as a unifying framework, linking human aging to natural decay, with broad implications for health and ecology. Recommendations include empirical validation with longitudinal data, machine learning for dynamic modeling, and interventions (e.g., cognitive training, reforestation) to counter entropy’s effects. This framework bridges disciplines, providing a novel perspective on life’s entropic trajectory.